ANALISIS PENYELENGGARAAN INOVASI PELAYANAN PUBLIK “MANGAN MENDOANE RINI” DALAM PERSPEKTIF BEST PRACTICE DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO - Diandya Prihatiningrum, Dewi; Djumiarti, Titik; Yuniningsih, Tri (Journal of Public Policy and Management Review, 2024)
The "Mangan Mendoane Rini" innovation is one of the superior innovations of RSUD Prof. Dr. Margono Soekarjo Purwokerto. This innovation has succeeded in overcoming problems such as stopping the practice of collusion between health workers, increasing the accuracy of drug/AHP procurement planning, increasing operational cost efficiency from 37% to 26%, reducing the type and number of expired drugs from 0.15% to 0.08%, increasing recording accuracy from 22% to 0%, increasing doctor's compliance with the formulary from 80% to 95% and increasing the community satisfaction index from 61% to 89%. This success has resulted in this innovation receiving many awards both at regional and national levels. This research aims to find out how to implement the "Mangan Mendoane Rini" innovation program based on Prasojo's (2007) best practice concept, by analyzing the dimensions of impact, partnership, sustainability, leadership and transferability. Data collection was carried out using in-depth interviews, observation and documentation. The results obtained are that the "Mangan Mendoane Rini" innovation has fulfilled and shown positive results in all dimensions which are the basis of the analysis. With the success of this innovation, RSMS continues to carry out updates and develop innovations aimed at improving service quality. Developments carried out include drug restrictions, BPJS e-claim prescription bridging, and free drug delivery. This innovation has been replicated by many other hospitals with the existence of SPO (Standard Operating Procedures) regarding replication and comparative studies.